(3efXheI aj GdJhMjOs - (3CHh GdMce EHQGgje GdCfUGQjs
(3ChdgG (B:s
(3MeO GdEdg hGLH dPGJg hTcQg Ydi YdG gHGJg fMeOg SHMGfg hfTcQI s
(3BNQgG (B:s
(3gh GdcJGH GdeHjf djS dg Yf GdgOi hGdUhGH ef hcH LGA Hg GdeUWai ef Gddg ai YTQjf MhdkG jJdhg ai UMa s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(249) s
Keywords: (3GdeLGejYs